The Simulation Study and Dynamic Analysis of Unified Power Flow Controller for Industrial and Educational Purposes - Ertay, M. M.; Aydogmus, Z. (Kaunas Univ Technology, 2012)
M. M. Ertay, Z. Aydogmus. The Simulation Study and Dynamic Analysis of Unified Power Flow Controller for Industrial and Educational Purposes // Electronics and Electrical Engineering. - Kaunas: Technologija, 2012. - No. 5(121). - P. 109-114. Unified Power Flow Controller (UPFC) is versatile and one of the advanced FACTS devices. In this study, dynamic analysis of UPFC is realized by MATLAB-Simulink simulation. For this purpose, a simulation model is presented that enable to be analysed of effects of device to power system in detail. Simulation model is a based on shunt current injection and series voltage injection. UPFC system dynamic model is based on a d-q synchronous reference frame. Developed simulation model enables to be analyzed effects of UPFC and the other converter based FACTS devices (STATCOM, SSSC,IPFC) to power system very simply. Besides, it can be used for education purpose in graduate studies which is about converter based FACTS devices. On the other hand, it can be used for industrial purpose in terms of power system engineers' investigations of effects of UPFC to power system. Simulated UPFC system consists of a load, UPFC and a power system with two machines. In simulation studies, functions of UPFC such as terminal voltage regulation and automatic power flow control is analysed and results are presented in case of graphics. Ill. 17, bibl. 18 (in English; abstracts in English and Lithuanian).
Keywords: Upfc